Principles of Stages of Legal Process - D. V. Slynko; L. I. Kalenichenko (Bulletin of Kharkiv National University of Internal Affairs)
The author has carried out theoretical study of the development of ideas in legal science on the principles of legal process; has studied the etymological meaning of the term of “principle”. The analysis of legal literature and the corresponding normative and legal material has been carried out. It has been noted that the principles of legal process are formed as a result of verified, reasoned and substantiated activities of authorized entities after the cognition of the patterns of procedural activities. Using the action of principles of legal process in the legal system as a criterion of classification, the author has singled out its general and special principles. The general principles of legal process include principles aimed at revealing the nature, character, nature of legal process. The special principles, in turn, include principles that reflect the functional orientation of the types of legal process and determine the organizational features, specifics of means and methods of carrying out procedural activities at its individual stages. Taking into account the organizational features, specifics of means and methods of carrying out procedural activities at its separate stages, such principles of stages of legal process as the principle of written form of consolidation, the principle of legal qualification, the principle of certification of result, the principle of urgency have been singled out. The author has provided characteristics and has revealed the content of these principles.